Encyclopaedia Britannica 2003 ultimate reference suite. (Encyclopaedia Britannica, 2003)
Contains Encyclopaedia Britannica, Britannica Student Encyclopedia, and Britannica Elementary Encyclopedia, 91,000 articles, dictionaries a world atlas and 21,000 images and videos.